Qualitative Study of a 4D Chaos Financial System - Fuchen Zhang; Gaoxiang Yang; Yong Zhang; Xiaofeng Liao; Guangyun Zhang (Complexity)
Some dynamics of a new 4D chaotic system describing the dynamical behavior of the finance are considered. Ultimate boundedness and global attraction domain are obtained according to Lyapunov stability theory. These results are useful in estimating the Lyapunov dimension of attractors, Hausdorff dimension of attractors, chaos control, and chaos synchronization. We will also present some simulation results. Furthermore, the volumes of the ultimate bound set and the global exponential attractive set are obtained.